USE OF VIRTUAL GUIDED SURGERY FOR A REHABILITATION OF A COMPLEX MAXILLARY FULL ARCH WITH IMMEDIATE LOADING - Cividini, Laura; Cantareli, Michele; de Alencar e Silva Leite, Pedro; Stutz, Carlos; Traczinski, Adriana; Sartori, Elisa (Brazilian Journal of Implantology and Health Sciences, 2025)
Advances in dentistry technology allow complex rehabilitations to be performed with greater safety and a high degree of precision, eliminating the need for corrective surgeries prior to rehabilitation with dental implants. By the use of digital workflow, it is possible to transfer the correct position of the implant to the surgical bed through a surgical guide, using digital equipment such as digital tomography and surgical planning software. Clinical case: The patient attended the clinic for functional and aesthetic rehabilitation. The clinical examination noted the presence of teeth 18, 15, 12, 11, 21, 22, 23, 25, 38, 35, 33, 32, 31, 41, 42, and 43 with generalized periodontal lesions and mobility. The tomographic examination showed low bone availability. To resolve the problem, extractions were initially performed and prior prosthetic planning included the use of dual tomography and the CoDiagnostiX software. Four implants (Helix Grand Morse, Neodent) were installed in the maxilla using a virtual surgical guide in immediate loading. The hybrid implant-supported prosthesis was manufactured using analog and digital flow, which allowed delivery in a few hours postoperatively and reproduced correct function and occlusion. Conclusion: Based on the experience gathered in conducting this case, it is possible to conclude that virtual guided surgery is a technique that optimizes the quality and precision of rehabilitation. In addition, it is minimally invasive in nature, providing comfort and safety during and after surgery, resulting in a good experience for the professional and the patient.